What causes cost overrun in transport infrastructure projects - Flyvbjerg, B; Holm, M; Buhl, S (2004)
Results from the first statistically significant study of the causes of cost escalation in transport infrastructure projects are presented. The study is based on a sample of 258 rail, bridge, tunnel and road projects worth US$90 billion. The focus is on the dependence of cost escalation on: (1) the length of the project-implementation phase, (2) the size of the project and (3) the type of project ownership. First, it was found, with very high statistical significance, that cost escalation was strongly dependent on the length of the implementation phase. The policy implications are clear: decision-makers and planners should be highly concerned about delays and long implementation phases because they translate into risks of substantial cost escalations. Second, projects have grown larger over time, and for bridges and tunnels larger projects have larger percentage cost escalations. Finally, by comparing the cost escalation for three types of project ownership—private, state-owned enterprise and other public ownership—it was shown that the oft-seen claim that public ownership is problematic and private ownership effective in curbing cost escalation is an oversimplification. The type of accountability appears to matter more to cost escalation than type of ownership.